2010
DOI: 10.1021/np100442x
|View full text |Cite
|
Sign up to set email alerts
|

Lagunamides A and B: Cytotoxic and Antimalarial Cyclodepsipeptides from the Marine Cyanobacterium Lyngbya majuscula

Abstract: Lagunamides A (1) and B (2) are new cyclic depsipeptides isolated from the marine cyanobacterium Lyngbya majuscula obtained from Pulau Hantu Besar, Singapore. The planar structural characterization of these molecules was achieved by extensive spectroscopic analysis, including 2D NMR experiments. In addition to Marfey's method and (3)J(H-H) coupling constant values, a modified method based on Mosher's reagents and analysis using LC-MS was deployed for the determination of the absolute configuration. Lagunamides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 20 publications
1
99
1
1
Order By: Relevance
“…Results shown above indicate that there was no significant effect of pre-exposure on invasion, maturation, or growth of the malaria parasite suggesting the selective action of extracts on Plasmodium falciparum with no significant toxicity against host red blood cells. 0.19 mM), lagunamide B (IC 50 ¼ 0.91 mM) (Tripathi et al, 2010a), and malyngolide dimer (Gutiérrez et al, 2010) (IC 50 19 mM) against P. falciparum appear to reinforce the possibilities of finding new antimalarial pharmacophores from L. aestuarii CNP 1005 (IC 50 ¼ 18 mg mL À1 ) isolated from coastal regions of Tamil Nadu. To the best of our knowledge, there are no antimalarial studies from the heterocystous Anabaena sp.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Results shown above indicate that there was no significant effect of pre-exposure on invasion, maturation, or growth of the malaria parasite suggesting the selective action of extracts on Plasmodium falciparum with no significant toxicity against host red blood cells. 0.19 mM), lagunamide B (IC 50 ¼ 0.91 mM) (Tripathi et al, 2010a), and malyngolide dimer (Gutiérrez et al, 2010) (IC 50 19 mM) against P. falciparum appear to reinforce the possibilities of finding new antimalarial pharmacophores from L. aestuarii CNP 1005 (IC 50 ¼ 18 mg mL À1 ) isolated from coastal regions of Tamil Nadu. To the best of our knowledge, there are no antimalarial studies from the heterocystous Anabaena sp.…”
Section: Discussionmentioning
confidence: 76%
“…More interestingly, marine Moorea producens (earlier known as Lyngbya majuscula Harvey in Hooker ex Gomont) has been found to exhibit potent antimalarial activity against Plasmodium falciparum and a number of antimalarial compounds such as lagunamides (Tripathi et al, 2010a), dragomabin (McPhail et al, 2007), and malyngolide (Gutiérrez et al, 2010) have been isolated from it. Likewise, antimalarial screening of 18 cyanobacterial strains showed that the methylene dichloride extract of Phormidium ectocarpi inhibited the malaria parasite (IC 50 ¼ 2.1 mg mL À1 ) (Papendorf et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Lagunamides are new cyclic depsipeptides isolated from the marine cyanobacterium Lyngbya majuscula collected from the western lagoon of Pulau Hantu Besar, Singapore [168,169]. These compounds exhibit potent biological activities, such as antimicrobial, antimalarial, cytotoxic, and neurotoxic properties, which make these marine cyanobacterial compounds interesting lead compounds for further development as antitumor therapeutics.…”
Section: Rcm Of Depsipeptidesmentioning
confidence: 99%
“…These compounds exhibit potent biological activities, such as antimicrobial, antimalarial, cytotoxic, and neurotoxic properties, which make these marine cyanobacterial compounds interesting lead compounds for further development as antitumor therapeutics. The originally assigned stereochemical configuration of lagunamide A (116a) [168] was revised by Dai et al [170] and turned out to be the C7 and C39 epimer (Scheme 27). So far, the (E)-olefin in lagunamide A has been installed via the Horner-Wadsworth-Emmons olefination, while Huang et al [151] designed a metathesis approach to introduce this double bond in its correct geometry.…”
Section: Rcm Of Depsipeptidesmentioning
confidence: 99%
“…The resulting mixture was evacuated with H 2 (g) and then stirred under H 2 (g) (1 bar) atmosphere for 12 hrs. The mixture was filtered through a celite pad and concentrated under reduced pressure to produce the title compound 5 (95% yield, 85:15 conversion from starting material) 1 …”
Section: -(4-(4-(5-((3as 4s 6ar)-2-oxohexahydro-1h-thieno [34-d]imentioning
confidence: 99%